ENGAGED MUSICAL LEADERSHIP AIMED AT TRANSFORMATIONS IN SOCIAL PROJECTS - Harder, Rejane; Feichas, Heloísa (Revista Gênero e Interdisciplinaridade, 2025)
The research reported here aimed to verify whether, and in what manner, music educators in the context of two social projects in Belo Horizonte, Minas Gerais, demonstrated in their teacher/student interactions characteristics of an engaged musical leadership, aiming at social transformations and creative learning. The research, of a qualitative nature, used the case study method, with the field research consisting of on-site observation of the activities in the referred projects. The research techniques consisted of observation and semi-structured interviews. The bibliographical research addressed engaged musical leadership with an emphasis on creative learning and the social impact of music making as a theoretical basis. From the interactions with the leaders and other actors of the projects studied, as well as the analysis of videos and documents, it was possible to identify in both, elements that indicate the presence of an engaged musical leadership, which aims at the social transformation of the project members and the existence of creative teaching and learning processes in their classes and musical and extramusical activities. The responses from the interviews, as well as the observations made and analyzed in light of the theoretical basis, led to the conclusion that much more can be done to prepare music teachers to work in social projects. The involvement with this research, as well as the conclusions from it, led to the idea of ​​implementing pedagogical actions in undergraduate music courses in the form of disciplines and extension activities that involve the immersion of students in the community.